2022
DOI: 10.1051/0004-6361/202142662
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent X-ray flares of the black hole candidate in the globular cluster RZ 2109 in NGC 4472

Abstract: We report on the systematic analysis of the X-ray observations of the ultra-luminous X-ray source XMMU J122939.7+075333 located in the globular cluster RZ 2109 in the Virgo galaxy NGC 4472. The inclusion of observations and time intervals ignored in previous works and the careful selection of extraction regions and energy bands have allowed us to identify new flaring episodes, in addition to the ones that made it one of the best black hole candidates in globular clusters. Although most observations are too sho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…As for the case of XMMU J122939.7+075333, the amount of mass accreted at every passage is very small, about 5.5 × 10 −10 M . As pointed out by Tiengo et al (2022), with these low values of mass getting accreted per passage, one such event can last for very long times, and XMMU J122939.7+075333 has indeed been active for more than two decades. Finally, although the available observations are sparse and often provide only shallow upper limits, the outbursts of J0054 seem to recur on a timescale of ≈5 months, which is the time interval between the two closest outbursts and cannot be ruled out by non-detections.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…As for the case of XMMU J122939.7+075333, the amount of mass accreted at every passage is very small, about 5.5 × 10 −10 M . As pointed out by Tiengo et al (2022), with these low values of mass getting accreted per passage, one such event can last for very long times, and XMMU J122939.7+075333 has indeed been active for more than two decades. Finally, although the available observations are sparse and often provide only shallow upper limits, the outbursts of J0054 seem to recur on a timescale of ≈5 months, which is the time interval between the two closest outbursts and cannot be ruled out by non-detections.…”
Section: Discussionmentioning
confidence: 96%
“…The TDE hypothesis could also explain the observed long-term X-ray variability. As invoked for XMMU J122939.7+075333 (Tiengo et al 2022), an object sharing many characteristics with J0054 (long-term variability, very soft X-ray emission, forbidden lines in the optical counterpart), a star on a highly eccentric orbit would be stripped of its material at every pericentre passage, thus producing recurrent flares.…”
Section: Discussionmentioning
confidence: 99%
“…They were first discovered in the nucleus of GSN 069 (Miniutti et al 2019), and since then there have been five more confirmed QPE hosts (Giustini et al 2020;Arcodia et al 2021Arcodia et al , 2024 and two candidates (Chakraborty et al 2021;Quintin et al 2023). Related properties, including recurring large X-ray outbursts and supersoft thermal spectra, have also been observed from a handful of other supermassive black holes (SMBHs; Terashima et al 2012;Tiengo et al 2022;Evans et al 2023;Guolo et al 2024).…”
Section: Introductionmentioning
confidence: 99%